1994
DOI: 10.1073/pnas.91.8.2900
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in human ovarian carcinoma.

Abstract: Telomeres fulfill the dual function of protecting eukaryotic chromosomes from illegitimate recombination and degradation and may aid In chromosome attachment to the nuclear membrane. We have previously shown that telomerase, the enzyme which synthesizes telomeric DNA, is not detected in normal somatic cells and that telomeres shorten with replicative age. In cells immortalized in vitro, activation of telomerase apparently stabilizes telomere length, preventing a critical destabilization of chromosomes, and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
292
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 594 publications
(306 citation statements)
references
References 30 publications
13
292
0
1
Order By: Relevance
“…Moreover, if telomere damage does play a role in triggering cell cycle arrest, one should expect the ability of a cell to maintain its telomeres to be important for the duration and/or severity of the arrest. While most somatic human cells cannot counteract telomere shortening, immortal cells, among them at least 85% of all tumor cells, do have this possibility mostly by activation of the telomere-elongating enzyme: telomerase (Counter et al, 1994;Shay and Bacchetti, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if telomere damage does play a role in triggering cell cycle arrest, one should expect the ability of a cell to maintain its telomeres to be important for the duration and/or severity of the arrest. While most somatic human cells cannot counteract telomere shortening, immortal cells, among them at least 85% of all tumor cells, do have this possibility mostly by activation of the telomere-elongating enzyme: telomerase (Counter et al, 1994;Shay and Bacchetti, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…2,6 Since telomerase activity is absent in most somatic cells, telomere shortening occurs in these cells. [7][8][9][10] In contrast, immortal tumor cell lines and germ cell tissues show high levels of telomerase activity, resulting in a stable telomere length and unlimited proliferation. 7,11 It was recently reported that human hematopoietic stem/progenitor cells and activated lymphocytes exhibit low levels of telomerase activity.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the enzyme telomerase has been attracting interest as another promising candidate marker (Counter et al, 1994). The 'telomere hypothesis' proposes that activation of telomerase is necessary for cells to become immortal or capable of extended proliferation (Rhyu, 1995;Shay et al, 1995).…”
mentioning
confidence: 99%